Developing a disaster education program for community safety and resilience: the preliminary phase - Abdul Nifa, Faizatul Akmar; Abbas, Sharima Ruwaida; Chong, Khai Lin; Othman, Siti Norezam (IP Publishing LLC, 2017)
Resilience encompasses both the principles of preparedness and reaction within the dynamic systems and focuses responses on bridging the gap between pre-disaster activities and post-disaster intervention and among structural/non-structural mitigation. Central to this concept is the ability of the affected communities to recover their livelihood and inculcating necessary safety practices during the disaster and after the disaster strikes. While these ability and practices are important to improve the community safety and resilience, such factors will not be effective unless the awareness is present among the community. There have been studies conducted highlighting the role of education in providing awareness for disaster safety and resilience from a very young age. However for Malaysia, these area of research has not been fully explored and developed based on the specific situational and geographical factors of high-risk flood disaster locations. This paper explores the importance of disaster education program in Malaysia and develops into preliminary research project which primary aim is to design a flood disaster education pilot program in Kampung Karangan Primary School, Kelantan, Malaysia.